Comparative study of Rb1, cyclin D1 and p16 immunohistochemistry expression to distinguish lung small‐cell carcinoma and large‐cell neuroendocrine carcinoma. Issue 2 (27th May 2022) - Papaxoinis, G; Bille, A; McLean, E; Nonaka, D
Abstract : Aims: Large‐cell neuroendocrine carcinoma (LCNEC) and small‐cell carcinoma (SCLC) of lung encompass high‐grade neuroendocrine tumour category and share several fundamental features. As both tumours may respond to different treatment modalities and show unique molecular alterations distinction between the two is clinically relevant, but can be challenging due to sampling and fixation issues and shared morphological features. Methods: Surgically resected primary SCLC ( n  = 129) and LCNEC ( n  = 27) were immunohistochemically stained with Rb1, cyclin D1 and p16 using tissue microarray (TMA), and expression patterns of the proteins were compared between the two to identify the discriminatory pattern. Results: All markers had high diagnostic accuracy; Rb1 was the highest followed by p16 and cyclin D1. The majority of SCLC had the pattern Rb1−/p16+/cyclin D1– and more than half of LCNEC had Rb1+/p16−/cyclin D1+. Overall, the expression pattern Rb1– and cyclin D1– was strongly associated with the diagnosis of SCLC, while the pattern Rb1+ and/or cyclin D1+ was strongly associated with LCNEC. The use of this simplified expression pattern leads to a diagnostic accuracy of 97.3%. p16 did not add to further discrimination. The heterogeneity in Rb1, cyclin D1 and p16 expression was insignificant in SCLCs compared with LCNECs. Conclusions: Use of Rb1, cyclin D1 and p16 immunohistochemistry can distinguish the two with high accuracy. Notably, the Rb1−/cyclin D1– pattern in given tumour sample would confirm the diagnosis of SCLC. Our results could be extrapolated and applied to routine diagnostic samples such as biopsies and cytology samples. Abstract :